Effect of Dapagliflozin on Clinical Outcomes in Patients With Chronic Kidney Disease, With and Without Cardiovascular Disease - McMurray, John J.V.; Wheeler, David C.; Stefánsson, Bergur V.; Jongs, Niels; Postmus, Douwe; Correa-Rotter, Ricardo; Chertow, Glenn M.; Greene, Tom; Held, Claes; Hou, Fan Fan; Mann, Johannes; Rossing, Peter; et al. (Circulation, 2021)
BACKGROUND: Dapagliflozin reduces the risk of end-stage renal disease in patients with chronic kidney disease. We examined the relative risk of cardiovascular and renal events in these patients and the effect of dapagliflozin on either type of event, taking account of history of cardiovascular disease. METHODS: In the DAPA-CKD trial (Dapagliflozin and Prevention of Adverse Outcomes in Chronic Kidney Disease), 4304 participants with chronic kidney disease were randomly assigned to dapagliflozin 10 mg once daily or placebo. The primary end point was a composite of sustained decline in estimated glomerular filtration rate ≥50%, end-stage kidney disease, or kidney or cardiovascular death. The secondary end points were a kidney composite outcome (primary end point, minus cardiovascular death), the composite of hospitalization for heart failure or cardiovascular death, and all-cause death. In a prespecified subgroup analysis, we divided patients into primary and secondary prevention subgroups according to history of cardiovascular disease. RESULTS: Secondary prevention patients (n=1610; 37.4%) were older, were more often male, had a higher blood pressure and body mass index, and were more likely to have diabetes. Mean estimated glomerular filtration rate and median urinary albumin-to-creatinine ratio were similar in the primary and secondary prevention groups. The rates of adverse cardiovascular outcomes were higher in the secondary prevention group, but kidney failure occurred at the same rate in the primary and secondary prevention groups. Dapagliflozin reduced the risk of the primary composite outcome to a similar extent in both the primary (hazard ratio, 0.61 [95% CI, 0.48-0.78]) and secondary (0.61 [0.47-0.79]) prevention groups (P-interaction=0.90). This was also true for the composite of heart failure hospitalization or cardiovascular death (0.67 [0.40-1.13] versus 0.70 [0.52-0.94], respectively; P-interaction=0.88), and all-cause mortality (0.63 [0.41-0.98] versus 0.70 [0.51-0.95], respectively; P-interaction=0.71). Rates of adverse events were low overall and did not differ between patients with and without cardiovascular disease. CONCLUSIONS: Dapagliflozin reduced the risk of kidney failure, death from cardiovascular causes or hospitalization for heart failure, and prolonged survival in people with chronic kidney disease, with or without type 2 diabetes, independently of the presence of concomitant cardiovascular disease. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT03036150.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cardiovascular diseases; heart failure; renal insufficiency; chronic; sodium-glucose transporter 2 inhibitors